Sorption of Pb(II) and Zn(II) Ions from Aqueous Solution by Tannin Resins - Turak, Fatma; Turhan, Kadir; Ozgur, Mahmure Usetun (SPRINGER, 2009)
Recently, the interest on biomaterials and especially in tannins was growing and some attractive results were obtained in the adsorption of some metals by tannin adsorbents. Tannins are widely distributed in nature and have multiple adjacent poly-hydroxyphenyl groups in their chemical structure which have extremely high affinity for heavy metal ions. This study will describe how tannin can be used as an effective zinc and lead sorbent by the use of tannin resins. Batch method was used in the experiments in which pH profile, adsorption time, adsorbent/liquid ratios, initial concentration of metal ions, adsorbent amount and temperature were investigated to determine binding properties of adsorbent for the Zn(II) and Pb(II) ions.
Keywords: Biomaterial; heavy metals; lead; resin; tannin; zinc; RECOVERY; URANIUM; REMOVAL; WATER; Biochemistry & Molecular Biology; Chemistry